Pengaruh Penanaman Nilai Moderasi Beragama Terhadap Sikap Toleransi Siswa di MA Banu Hasyim Waru Sidoarjo - Afif Usfiyanto; Yuliastutik Yuliastutik (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
MA Banu Hasyim students have a very high tolerance attitude in every socio-cultural interaction at school. This is based on the instillation of the value of religious moderation which is implemented through the subjects of Citizenship Education and Islamic Religious Education. The aim of this research is to find out how the value of religious moderation is instilled at MA Banu Hasyim Waru Sidoarjo, to find out how students' attitudes of tolerance are at MA Banu Hasyim Waru Sidoarjo, and to find out how the instillation of religious moderation values is on students' tolerance attitudes at MA Banu Hasyim Waru Sidoarjo. By using quantitative research methods with a correlation approach. The sample in this research was all MA Banu Hasyim Waru Sidoarjo students because it was a population study. The variable The data collection technique uses questionnaires and documentation. Based on the data analysis carried out, it is known that the cultivation of religious moderation values at MA Banu Hasyim Waru Sidoarjo is going "well", this is based on the percentage results of 68.6% in the interval range 68.01% - 84.00%. Furthermore, the level of tolerance attitude Students at MA Banu Hasyim Waru Sidoarjo are in the "good" category, this is proven by the percentage value of 69.6% which is in the range 68.01% - 84.00%. Judging from the results of calculating the product moment correlation hypothesis test, it states There is an influence of instilling the value of religious moderation on the tolerance attitude of students at MA Banu Hasyim Waru Sidoarjo of 0.974. This value is in the range of 0.90 - 1.00 so it can be said that "there is a very strong or high relationship between the cultivation of religious moderation values and students' attitudes of tolerance at MA Banu Hasyim Waru Sidoarjo.